Malaria in Pregnancy. Issue 4 (2005) - Alvarez, Jesus R.; Al-Khan, Abdulla; Apuzzio, Joseph J.
Abstract : Recently, there has been a resurgence of malaria in densely populated areas of the United States secondary to human migration from endemic areas where factors such as cessation of vector control, vector resistance to insecticides, disease resistance to drugs, environmental changes, political instability, and indifference, have played a role for malaria becoming an overwhelming infection of these tropical underdeveloped countries. It is important for health care providers of gravida to be alert of the disease and its effects on pregnancy.